2005
DOI: 10.1007/s00420-004-0581-7
|View full text |Cite
|
Sign up to set email alerts
|

Effort?reward imbalance at work and job dissatisfaction in Chinese healthcare workers: a validation study

Abstract: Based on the results of this study the Chinese version of the ERI questionnaire is considered a reliable and valid instrument for measuring psychosocial stress at work. It is applicable to Chinese working populations and, in particular, to the healthcare sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
135
6
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 35 publications
15
135
6
8
Order By: Relevance
“…This latter distinction is important, since a broader approach may be needed to address these issues if they are common features of a hospital or health care system. The ER ratios returned from this study exceed those seen in many recent international studies of health care staff such as those conducted in China, Mongolia, Germany and France, with only Greek health care workers exceeding our values [24,25]. The mean over-commitment scores were similar to those of other European health care and public sector workers.…”
Section: Discussionsupporting
confidence: 56%
“…This latter distinction is important, since a broader approach may be needed to address these issues if they are common features of a hospital or health care system. The ER ratios returned from this study exceed those seen in many recent international studies of health care staff such as those conducted in China, Mongolia, Germany and France, with only Greek health care workers exceeding our values [24,25]. The mean over-commitment scores were similar to those of other European health care and public sector workers.…”
Section: Discussionsupporting
confidence: 56%
“…Job stressors were assessed using the Chinese version of the 23-item effort-reward imbalance questionnaire (ERI-Q) developed by Li Jian et al 20) , in accordance with Siegrist's ERI-Q. The ERI-Q consists of three scales termed extrinsic effort representing job demands imposed on the employee (6 items), reward which consists of income, respect, job security and career opportunities (11 items), and overcommitment which defines a set of attitudes, behaviors, and emotions reflecting excessive striving in combination with a strong desire for approval and esteem (6 items).…”
Section: Job Stressmentioning
confidence: 99%
“…According to this model, an imbalance between high efforts and low rewards, and/or high levels of overcommitment increases the risk of CHD. The Chinese version of the ERI questionnaire has been evaluated and is considered a reliable and valid instrument for measuring psychosocial stress at work in the Chinese working population 20,21) .We have examined the association between the job stressors evaluated by the ERI model and CHD assessed by coronary angiography, and found that ERI may act as a CHD risk factor in the Chinese population 22,23) . However, little is known about the effect of ERI on early atherosclerosis.…”
mentioning
confidence: 99%
“…Such findings would underline the evolutionary old 'grammar' of social exchange that may be rooted in distinct structures of the human brain (Cosmides and Tooby, 1992). Currently, a number of findings from observational studies confirm that effortreward imbalance at work is associated with elevated risks of stress-related disorders in Japanese (Tsutsumi et al, 2001), Chinese (Xu et al, 2004;Li et al, 2005), South Korean (Eum et al, 2007), Thay (Buapetch et al, 2008) and Brazilian (Chor et al, 2007) working populations, thus lending support to the idea that the experience of unfair exchange results in negative emotions and adverse well-being cross-culturally in similar ways. This discovery is of interest in view of the process of economic globalisation and associated trans-national labour market mobility.…”
Section: Brief Summary Of Empirical Evidence On Health-adverse Effectsmentioning
confidence: 85%